(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
This study tackles the problem of the relationship between history science and cultural development in independent Algeria through highlighting the role of history science in establishing and developing cultural development projects in post-independent Algeria. This is due to the fact that history is an essential scientific subject, an important educational instrument and an effective development tool to promote the cultural climate and activate development and construction projects in this field. It is no secret that the fulfilment of history has remained the true starting point for cultural development in independent Algeria, often making historical culture a necessary background (cultural development).